A Same Other, Another Same: Walter Benjamin and Maurice Blanchot on Translation. (April 2014) - Liska, Vivian; Conen, Naomi
<x xml:space="preserve">Abstract</x> Even though Walter Benjamin and Maurice Blanchot count among the most important literary critics of the past century and shared many concerns, they have rarely been considered together. There is, however, evidence that Blanchot read parts of Benjamin's writings and was inspired by them. Blanchot's most extensive references to Benjamin appear in a text entitled "Translating." This essay was composed on the basis of notes that Blanchot took while reading Benjamin's essay "Die Aufgabe des Übersetzers" and that have remained unpublished. These notes, which consist mainly of translations of passages from Benjamin's essay are a rich source of insight into Blanchot's reading process, which resulted in a powerful affirmation as well as a radical transfiguration of Benjamin's theory of translation. They also shed light on the similarities and differences between the two thinkers' respective theories of translation, their philosophies of language, and the divergent traditions in which their thinking is embedded.